Pengembangan Sistem Pendidikan Pesantren dalam Perubahan Sosial - Mujamil Qomar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2010)
Pesantren as a system of education has reciprocity with the other system. pesantren education system changes seen in the pattern of adaptation which may range from a very gradual adaptation to change very responsive. the adaptation of changes that occur the question is whether the boarding school on the subject or object position. when included in the formal areas, mobility was still limited to boarding school graduates in the sector, the religious department, and then only limited, if compared with other education. for that, the next boarding schools not only prepare the formal sector is limited, but must meet the needs of the open in the informal sector such as public and private.